Experimental manipulation of female tail length did not cause differential allocation by males in the barn swallow. (5th December 2017) - Hasegawa, Masaru; Arai, Emi; Nakamura, Masahiko
Abstract: The evolution and maintenance of female ornamentation has attracted increasing attention, because the previous explanation, that is a non‐functional copy of functional male ornamentation, seems insufficient to explain female ornamentation. A post‐mating sexual selection, differential allocation, may be more common than pre‐mating sexual selection, but few studies have investigated differential allocation by males. Here, we studied differential allocation of incubation investment by male barn swallows Hirundo rustica, a model species for the study of sexual selection, because our previous correlative study demonstrated a positive relationship between female tail length and male incubation investment. We manipulated the length of the outermost tail feathers in females after clutch completion and examined whether males adjust incubation investment according to female ornamentation. Because extra‐pair paternity is virtually absent in the study population, we were able to study differential allocation based on the tradeoff between current and future reproductive investments, rather than the tradeoff between current paternal investment and additional mating effort. The experimental treatment had no significant effect on male nest attentiveness, whereas female tail length before manipulation predicted male nest attentiveness. The observed pattern is consistent with differential access; that is, well‐ornamented individuals have greater access to mates with high reproductive (parental) ability, rather than differential allocation during incubation. Alternatively, males can directly assess eggs in their nests, and thus, as seen in other species, males might adjust their incubation investment based on the egg characteristics of long‐tailed females.